2021
DOI: 10.3390/cancers13112787
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Lipid Metabolite Profiles to Predict Outcomes in Patients Undergoing Interventional Therapy for a Hepatocellular Carcinoma (HCC): A Substudy of the SORAMIC Trial

Abstract: Background: This exploratory study aimed to evaluate lipidomic and metabolomic profiles in patients with early and advanced HCCs and to investigate whether certain metabolic parameters may predict the overall survival in these patients. Methods: A total of 60 patients from the prospective, randomized-controlled, multicenter phase II SORAMIC trial were included in this substudy; among them were 30 patients with an early HCC who underwent radiofrequency ablation combined with sorafenib or a placebo and 30 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that dysregulated metabolism is a hallmark of cancer, especially in HCC (16)(17)(18), for example, glycolytic pathway (9) and lipid metabolism pathway (19) were found to be upregulated in HCC, and targeting these pathways may have therapeutic potential. In our study, we performed more detailed research and found that metabolic pathways were activated or inhibited in different immune subtypes of HBV-HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that dysregulated metabolism is a hallmark of cancer, especially in HCC (16)(17)(18), for example, glycolytic pathway (9) and lipid metabolism pathway (19) were found to be upregulated in HCC, and targeting these pathways may have therapeutic potential. In our study, we performed more detailed research and found that metabolic pathways were activated or inhibited in different immune subtypes of HBV-HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The first study recruited 60 HCC patients to identify serum metabolites that were associated with therapeutic outcomes of HCC after TACE treatment. It was found that higher levels of total cholesterol, low density lipoprotein cholesterol, and low-density lipoprotein particles were associated with a poorer overall survival ( 106 ). Another 1 H-NMR-based study aimed to investigate the metabolic alterations in plasma of recurrent or metastatic HCC patients after TACE treatment or post-surgery.…”
Section: Hcc Metabolomics For Biomarkers Discoverymentioning
confidence: 99%